All Days 1983
DOI: 10.2118/11787-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Polyacrylamide Gel Syneresis Determined by C-13 NMR

Abstract: Polyacrylamide gels have been used for some time to reduce water cut in production wells and control profiles in injectors. Formations up to 150°F have been treated rather routinely. Recently, interest has developed in using these gels at higher temperatures in formations containing relatively hard brines. We have investigated the changes in hydrolysis of polyacrylamide polymers and gels crosslinked with trivalent chromium with C-13 NMR. This method is a direct way to correlate changes in the gel composition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Because of the presence of a large number of hydrophilic groups on the polymer chain, gels tend to swell when in contact with water. As the salinity of the formation water and amide group hydrolysis increase, the carboxylic acid groups react with divalent ions such as Ca 2+ and Mg 2+ , resulting in a decrease in the gel hydrophilicity [ 20 ]. The gel elastic potential is greater than the mixing potential, resulting in the expulsion of solvent from the gel network or syneresis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the presence of a large number of hydrophilic groups on the polymer chain, gels tend to swell when in contact with water. As the salinity of the formation water and amide group hydrolysis increase, the carboxylic acid groups react with divalent ions such as Ca 2+ and Mg 2+ , resulting in a decrease in the gel hydrophilicity [ 20 ]. The gel elastic potential is greater than the mixing potential, resulting in the expulsion of solvent from the gel network or syneresis.…”
Section: Resultsmentioning
confidence: 99%
“…The carboxylate groups produced by hydrolysis of the acrylamide groups on the polymer can further interact with divalent ions, leading to gel syneresis. This syneresis can also be considered a result of over-crosslinking between divalent ions and carboxylates [ 20 , 21 ]. This form of syneresis is particularly related to the use of polymers in hard brines at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The HPAM/inorganic metal ion gel system is usually used as an anatomical water-plugging agent or fracturing fluid in oilfield production, and the reaction mechanism is that carboxylate and high-valent metal ions in the polyacrylamide undergo a crosslinking reaction through ligand bonds [12][13][14][15], among which the most reported related studies use a chromium acetate crosslinker. DiGiacomo [16] characterized polyacrylamide and trivalent chromium ion gels by a 13 C nuclear magnetic resonance based on the paramagnetism of Cr 3+ and found that chromium ions in the complexed or free state crosslinked with carboxylates on HPAM molecules through ligand bonding to form a three-dimensional reticulated gel skeleton, yielding a strong gel with good viscoelasticity. The chromium ion crosslinking agent is usually used in reservoirs with formation temperatures below 70 • C. Too-high gel formation temperatures will lead to a violent reaction, and it is difficult to control its gel formation time and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the stability and strength of chromium gels will decline sharply, which will greatly reduce the plugging period. DiGiacomo [ 24 ] found that in the presence of calcium and magnesium ions, the dehydration of chromium gels was intensified and suggested that this was due to Ca 2+ and Mg 2+ ions reacting with the carboxyl group in PAM and producing carboxylates with low water solubility. Wang [ 25 ] investigated the impact of calcium chloride on the dehydration behavior and the microstructure of PAM/Cr 3+ gel.…”
Section: Introductionmentioning
confidence: 99%